User Perceptions of the Service Quality of Soepardjo Roestam Library, Ministry of Home Affairs - Dyah Kusuma Wardani (Indonesian Journal of Librarianship, 2025)
Background/Problem Statement: The contemporary perception of the library differs from its historical representation.  Today, libraries must contend with digital information media that is accessible at any time and from any location.  Furthermore, the Soepardjo Roestam Library, a specialized library with restricted segmentation, must sustain the quality of its services to remain beneficial for its consumers.  User perceptions of service quality serve as a key standard for enhancing library services. Purpose:   This research examines library users' perceptions of service quality at the Soepardjo Roestam Library.   Method: Concurrent mixed techniques are employed as the analytical tool.  This methodology integrates both quantitative and qualitative techniques.  The quantitative method involves a survey of 80 participants utilizing the Grand Mean technique.  The qualitative method enhances the analysis of quantitative data through interviews with four active users.  This study employs Charles Grönroos' service quality theory as a framework for its analysis of service quality. Result:  The results indicate that the overall mean value of consumers' perceptions of the Technical Quality and Functional Quality aspects is at a satisfactory level.  Meanwhile, the interview results corroborate the quantitative data.  The interviews reveal other conclusions, specifically that consumers desire enhancements in several aspects concerning the perception of exclusivity and the deficiency of social interaction with library services.  Moreover, users expressed aspirations and suggestions for promotion.  Conclusion:   The study's results indicate that users are highly happy with the service quality of the Soepardjo Roestam Library.  This finding affirms the continued necessity of the Soepardjo Roestam library.Keywords: Service Quality, Perception, Exclusive Library